Design improvement for power window mechanism-scissor type - Badrul Hisyam, Ahmad (2009)
Power window regulator is a mechanism for raising and lowering door glass. It consists of a set of gear, electric motor and door sash channels. For this project, power window design of the Proton Gen-2 was selected, where the improvement had been made at main arm and slider. The main arm and slider was designed using CAD software. Then, the design was analyzed using FMEA method and FEA (ALGOR) software. These analyses were done to find the best design that can optimize the operation for the stress analysis. There is one design for main arm and two designs for slider had been done. The analysis showed that both of the new designs are better compared to current design. For the both designs, the result showed that when force are applied, the displacement of improvement design that occur is lowest than current design. In conclusion, this improvement can reduce the cost of repairing because the improvement made can hopefully reduce the failure occurrence for that specific power window mechanism.